A Comprehensive Comparative Study for the Authentication of the Kadsura Crude Drug - Liu, Jiushi; Wei, Xueping; Zhang, Xiaoyi; Qi, Yaodong; Zhang, Bengang; Liu, Haitao; Xiao, Peigen (Frontiers in Pharmacology, 2019)
The stems and roots of Kadsura species have been used as the folk medicine in TCM and have good traditional efficacy and medicinal application with a long history. Among these species, K. coccinea, K. heteroclita and K. longipedunculata are the most widely distributed species in the regions of south and southwest China. Owing to their similar appearance, the crude drugs are often confusedly used by some folk doctors, even some pharmaceutical factories. To discriminate the crude drugs, haplotype analysis based on cpDNA markers and ITS was firstly employed in this study. Generic delimitation, interspecific interrelationships, and the identification of medicinal materials between K. longipedunculata and K. heteroclita remained unresolved by the existing molecular fragments. The original plant could be identified through the morphological character of flower, fruit and leaf. However, in most situation collectors have no chance to find out these characters due to lack of reproductive organs, and have no experience with the minor difference and transitional variation of leaf morphology. The chemical characterization show that the chemometric of chemical composition owned higher resolution to discriminate three herbs of Kadsura species. In conclusion, this integrative approach involving molecular phylogeny, morphology and chemical characterization could be applied for authentication of the Kadusra. Our study suggests the use of this comprehensive approach for accurate characterization of this closely related taxa as well as identifying the source plant and confused herbs of TCM